Technology-Enhanced Learning and Curriculum Innovations: Strategies for Alternative Education and Sustainable Development - Iroriteraye-Adjekpovu, Janice Imizuokena; Nwabuaku, Louis (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
This paper examined the potential benefits of technology-enhanced learning (TEL) as a curriculum innovation for achieving sustainable development and alternative education. The study adopted the descriptive qualitative research approach and responded to two research questions by reviewing related works of literature. The concept of TEL was thus explored, as well as how it can be used to support equal opportunities for all students, enhance their engagement and motivation, and develop their critical thinking, and problem-solving skills. Furthermore, the study scrutinized the implications of curriculum innovations on alternative education models, particularly their capacity to promote social and environmental sustainability. It was suggested that the Nigerian government develop a national policy framework and action plan for TEL that aligns with the national vision, goals, and priorities for education and sustainable development. The research thus fills a knowledge gap that informs and guides education stakeholders on the need to integrate technology and innovative curriculum designs to advance sustainable development and alternative education.